The American Perception of Class - Vanneman, Reeve (Temple University Press, 1987)
Scholars and nonacademics alike have usually assumed that the American working class does not think of itself as a coherent class opposed to the dominant powers in American society-in short, that it is not class conscious. In international perspective, the American working class appears docile and complacent. It has never supported a strong socialist movement; a weak union movement has limited itself to simple wage demands; and class conflict here has rarely threatened to explode into a social revolution. Both radicals and mainstream scholars have explained this American exceptionalism by the conservative psychology of the American worker. This provocative book presents a new vision of the American working class. The American Perception of Class offers a radically new interpretation of American class conflict and criticizes earlier analyses for psychologizing the problem and "blaming the victims" for their subordination. It marshals a great variety of evidence, primarily from national surveys, to demonstrate that, contrary to what almost everybody has assumed, American workers are indeed class conscious. They have not been so beguiled by images of a classless society that they can no longer recognize the divide that separates them from their middle class and corporate bosses; nor have they been swallowed up by an affluent middle class; and they have not been so divided by racial and ethnic loyalties, or gender specific interests that they have forgotten their common class position. Finally, the book suggests a new approach to class conflict in America-one not based on the psychology of the American worker but on the strength of American business and its capacity to overwhelm or redirect any challenge from below. No other working class has faced such a formidable opponent.